2002
DOI: 10.1182/blood-2002-02-0632
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid in acute promyelocytic leukemia: long-term outcome and prognostic factor analysis from the North American Intergroup protocol

Abstract: We previously reported a benefit for alltrans retinoic acid (ATRA) in both induction and maintenance therapy in patients with acute promyelocytic leukemia (APL). To determine the durability of this benefit and identify important prognostic factors, long-term follow-up of the North American Intergroup APL trial is reported. A total of 350 patients with newly diagnosed APL were randomized to either daunorubicin and cytarabine (DA) or ATRA for induction and then either ATRA maintenance or observation following co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
275
2
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(298 citation statements)
references
References 39 publications
11
275
2
10
Order By: Relevance
“…Organ infiltration by leukemic cells, however, produces a life-threatening therapeutic complication known as retinoic acid syndrome that affects many patients with APL (11)(12)(13). ATRA-induced APL cell extravasation was found to be due to the increased adhesion and motility of these cells as compared with their undifferentiated counterparts (14 -16).…”
mentioning
confidence: 99%
“…Organ infiltration by leukemic cells, however, produces a life-threatening therapeutic complication known as retinoic acid syndrome that affects many patients with APL (11)(12)(13). ATRA-induced APL cell extravasation was found to be due to the increased adhesion and motility of these cells as compared with their undifferentiated counterparts (14 -16).…”
mentioning
confidence: 99%
“…The introduction of ATRA in 1985 has become a paradigm of molecular targeted therapy and transformed a once highly fatal disease to the most curable subtype of adult AML. Evidences from several randomized clinical trials indicate that maximal improvement in the CR rate, disease free and overall survival is obtained from a combination of ATRA plus cytotoxic chemotherapy [1,2]. A similar treatment strategy was employed in our patient.…”
Section: Discussionmentioning
confidence: 83%
“…Untreated, it runs a fatal course of only weeks, with most succumbing to severe hemorrhagic diathesis. The introduction of all-trans retinoic acid (ATRA) in the frontline treatment has revolutionized the management of APL with dramatic improvement in complete remission rate and overall survival [2].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these experiences and the results of single agent anti-APL efficacies of ATRA and arsenic trioxide [59], investigators evaluated the addition of ATRA to chemotherapy during both induction and/or consolidation [60][61][62], the addition of arsenic trioxide during consolidation therapy [63], and the use of nonchemotherapy regimens including ATRA, arsenic trioxide, and GO. Comparative studies showed that the addition of ATRA to chemotherapy during induction and or consolidation improved survival [60][61][62], and that the addition of arsenic trioxide during consolidation in CR also improved survival.…”
Section: Acute Promyelocytic Leukemiamentioning
confidence: 99%
“…Comparative studies showed that the addition of ATRA to chemotherapy during induction and or consolidation improved survival [60][61][62], and that the addition of arsenic trioxide during consolidation in CR also improved survival. In the late 1990s, the combination of idarubicin (or other anthracyclines) and ATRA (AIDA regimen) became standard of care in APL (with or without the addition of high-dose cytarabine and maintenance with POMP in APL subsets) [64].…”
Section: Acute Promyelocytic Leukemiamentioning
confidence: 99%